Application of potassium through irrigation water on the melon crop - Pinto, José Maria; Soares, José Monteiro; Choudhury, Eliane Nogueira; Pereira, José Ribamar (Pesquisa Agropecuaria Brasileira, 1993)
In order to evaluate the effects of the application of potassium through irrigation water on the melon crop (Cucumis melo L.), cv. Eldorado 300, a study was carried out at Bebedouro Experimental Station, Embrapa-CPATSA, Petrolina, PE, Brazil. Three periods of fertirrigation were used- up to 30, up to 42 and up to 55 days after germination. Phosphorus and 55% of the nitrogen were applied at planting time and the 45% remaning nitrogen were applied 30 days after planting. The trickle irrigation system was used. The highest yields were 28.05 and 25.18 ton./ha for the two greatest periods of fertirrigation, respectively. The application of potassium through irrigation water did not affect the chemical characteristics of the fruit, such as soluble solids content, total acidity and pH.